The Effect of Transcutaneous Electrical Nerve Stimulation (TENS) And Kinesiology Taping (KT) Therapy on Shoulder Pain on Badminton Athletes at The OK Clinic Pringsewu - Dwiningrum, Riza; Safutri, Wina (Universitas Aisyah Pringsewu, 2022)
Sport is an activity that is generally often carried out by the community, its existence has now become a part of community life. Injuries generally occur due to collisions, whether physical contact or falls. Badminton sport consists of various types of movements, including movements that involve the arms. This movement if done continuously will cause injuries such as shoulder pain. Kinesio taping relieves lower back pain after two up to three days of use. Kinesio taping peaks after 24 hours of use and will decrease in function after four days. Transcutaneous Electrical Nerve Stimulation (TENS) therapy has been shown to reduce various types of pain in 15-30 minutes. The research objective was to determine the effect of TENS and Kinesio taping on the shoulder pain of badminton athletes at the OK clinic Pringsewu. This type of research is a quasi-experimental study with a non-equivalent pre and post-control group design. The sampling technique was purposive sampling method. The number of subjects was divided into two groups (TENS and Kinesio taping). TENS used digital TENS, kinesio taping used 'Spol Kinematics Tex. The results showed that the mean difference of shoulder pain in badminton athletes before and after being given TENS therapy in badminton athletes at the OK clinic showed that the pre-test and post-test p values were less than 0.05. The difference in the mean level of shoulder injury pain in badminton athletes before and after kinesio taping therapy in badminton athletes at the OK Clinic Pringsewu. The results show that the P-value is 0.007 (P less than 0.005), this indicates that there is a difference between before and after the use of kinesio tapping. Based on this, it can be concluded that there is a difference in decreasing the scale of shoulder pain between TENS therapy and kinessio tapping. TENS is better with a p-value of 0.006. Abstrak: Olahraga merupakan kegiatan yang umumnya sering dilakukan oleh masyarakat, keberadaannya kini telah menjadi bagian dari kehidupan masyarakat. Cedera umumnya terjadi akibat benturan, baik kontak fisik maupun jatuh. Olahraga bulutangkis terdiri dari berbagai jenis gerakan, termasuk gerakan yang melibatkan lengan. Gerakan ini jika dilakukan terus menerus akan menimbulkan cedera seperti nyeri bahu. Kinesio taping meredakan nyeri punggung bawah setelah dua hingga tiga hari digunakan. Kinesio tapping mencapai puncaknya setelah 24 jam penggunaan dan akan berkurang fungsinya setelah empat hari. Transcutaneous Electrical Nerve Stimulation (TENS) telah terbukti mengurangi berbagai jenis nyeri dalam 15-30 menit. Tujuan penelitian untuk mengetahui pengaruh TENS dan Kinesio taping terhadap nyeri bahu pada atlet bulutangkis di OK Clinic Pringsewu. Jenis penelitian ini adalah penelitian quasi eksperimen dengan desain non-equivalent pre and post control group design. Teknik pengambilan sampel menggunakan metode purposive sampling. Jumlah subjek dibagi menjadi dua kelompok (TENS dan Kinesio taping). TENS menggunakan TENS digital, kinesio taping menggunakan 'Spol Kinematics Tex. Hasil penelitian menunjukkan bahwa perbedaan rerata nyeri bahu pada atlet bulutangkis sebelum dan sesudah diberikan terapi TENS pada atlet bulutangkis di klinik OK menunjukkan bahwa pre-test dan post-test nilai p adalah kurang dari 0,05. Perbedaan rerata tingkat nyeri cedera bahu pada atlet bulutangkis sebelum dan sesudah terapi kinesio taping pada atlet bulutangkis di OK Clinic Pringsewu. Hasil penelitian menunjukkan nilai P sebesar 0,007 (P kurang dari 0,005), hal ini menunjukkan adanya perbedaan antara sebelum dan sesudah penggunaan sadap kinesio. Berdasarkan hal tersebut dapat disimpulkan bahwa terdapat perbedaan penurunan skala nyeri bahu antara terapi TENS dan kinesio tapping. TENS lebih baik dengan nilai p 0,006.